Modulated model predictive current control of an indirect matrix converter with active damping - Di, Zhengfei; Rivera, Marco; Dan, Hanbing; Tarisciotti, Luca; Zhang, Kehan; Xu, Demin; Wheeler, Patrick (2017)
A modulated model predictive control (M²PC) scheme for an indirect matrix converter is proposed in this paper, including an active damping method to mitigate the input filter resonance. The control strategy allows the instantaneous power control and the output current control at the same time, operating at a fixed frequency. An optimal switching pattern is used to emulate the desired waveform quality features of space vector modulation and achieve zero-current switching operations. The active damping technique emulates a virtual resistor which damps the filter resonance. Simulation results present a good tracking to the output-current references, unity input displacement power factor, the low input-current distortions and a reduced common-mode voltage (CMV).